Chronicles in ivory: estimating the age of narwhals (Monodon monoceros) through stochastic modeling of seasonally varying trace elements - Reiter, Lars N.; Thomsen, Tonny B.; Heredia, Benjamin D.; Samson, Adeline; Wielandt, Daniel K. P.; Heide-Jørgensen, Mads Peter; Ditlevsen, Susanne; Garde, Eva (Frontiers in Marine Science, 2025)
IntroductionAge estimation is an important tool for understanding the life history of animal populations, and several techniques have been developed, each with its own strengths and limitations.MethodsIn this study, we apply a novel age estimation method that utilizes trace element signals with seasonal components obtained through laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) on tusks of 16 narwhals. We model tusk growth as a stochastic process that, by hypothesis, tracks the number of elapsed annual cycles. For each tusk, we estimate this process in order to derive model-based age estimates. ResultsWe show that this method provides objective and reproducible age estimates without requiring visually distinguishable growth layers. Age estimates are compared with those from other methods, specifically manual counting (visual reading) of growth layers, radiocarbon dating, and using aspartic acid racemization. Our model provided age estimates ranging from 16 to 60 years of age and showed strong agreement with manual counts for 14 of 16 individuals, with two critical exceptions differing by 9 and 14 years, respectively. DiscussionWe end with a discussion of modeling challenges and deficiencies related to this particular tusk dataset. Although demonstrated on narwhal tusks, we discuss how this method can be generalized to other mineralized materials with a layered structure.